Analisis Penerapan PSAK Syariah No. 102 Akad Murabahah pada KSPPS BMT Al-Ittihad Cabang Rumbai Pekanbaru - Salmaa Aliyah; Khadijah Ath Thairah (Yayasan Almanar Pujud, 2024)
BMT Al-Ittihad Rumbai Pekanbaru is one of the Islamic financial organizations and operates with Islamic sharia principles, with one of the Murabahah financing transactions. This study aims to find out how the application of PSAK 102 and analyze the suitability of the treatment of murabahah contracts at BMT Al-Ittihad Rumbai Pekanbaru with PSAK 102.This research uses a qualitative method with a descriptive approach, namely by describing the implementation of the murabahah financing program at BMT Al-Ittihad Rumbai Pekanbaru, analyzing the suitability of accounting treatment on recognition, measurement, presentation, and disclosure of Murabahah financing at BMT Al-Ittihad Rumbai Pekanbaru with PSAK 102 through interviews, observation, and documentation. The results of this study indicate that the accounting treatment of Murabahah at BMT Al-Ittihad Rumbai Pekanbaru is not fully in accordance with the accounting treatment of Murabahah in PSAK 102 which includes recognition and measurement of Murabahah, while the presentation and disclosure are in accordance with PSAK 102.